(untitled) (Journal of the College of Basic Education, 2022)
Summary of the research:Social persuasion occurs within intentional messages initiated by the caller in the hope of influencing The receiver and social persuasion is practiced on individuals through comments or behavioral modelsThe effect depends to a large extent on the experience and credibility of the sources of persuasion and the professional hesitation it hasThe individual in it is unable to make a decision related to the profession; The process of choosing a profession is very importantIt affects the future of students because it meets their needs and tendencies. The current research aimed to identifySocial persuasion and professional hesitation among your university students, as well as finding differences in persuasionSocial and occupational frequency, as well as the relationship between them according to the variables of males and females and specializationScientific and human